Edukasi Strategi Pemberian Makanan Sehat Pada Anak di Kelompok Bermain, Raudhatul Athfal dan SDIT Darul Ulum - Yuliani, Feri Catur; Putri Kusumawati P; Aminatul F; Bayu Hartono (JCSE: Journal of Community Service and Empowerment, 2024)
A balanced diet is a combination of daily foods that contain sufficient nutrients for a child's body. A balanced diet is important to prevent nutritional problems. It involves the principles of food types, physical activity, hygiene, and maintaining normal body weight. To keep children healthy, providing them with health-promoting nutrients through a balanced diet will help them reach their maximum potential. Community service activities entitled Education on Healthy Food Giving Strategies for Children in Playgroups, Raudhatul Athfal and SDIT Darul Ulum which aims to provide education, especially about healthy food for children, participants in this community service activity are students of Playgroups, Raudhatul Athfal and SDIT Darul Ulum along with parents of new students of Playgroups, Raudhatul Athfal Darul Ulum. The educational methods used in this community service activity include socialization, lectures, questions and answers, sharing experiences, and problem solving. The results of the implementation of community service activities on "Education on Healthy Food Providing Strategies for Children in Playgroups, Raudhatul Athfal and SDIT Darul Ulum" have been implemented in accordance with the planning prepared by the community service team. Participants became aware and understood about the strategy of providing healthy food for children.